Concert halls with strong and lateral sound increase the emotional impact of orchestra music - Pätynen, Jukka; Lokki, Tapio (The Journal of the Acoustical Society of America, 2016)
An audience's auditory experience during a thrilling and emotive live symphony concert is an intertwined combination of the music and the acoustic response of the concert hall. Music in itself is known to elicit emotional pleasure, and at best, listening to music may evoke concrete psychophysiological responses. Certain concert halls have gained a reputation for superior acoustics, but despite the continuous research by a multitude of objective and subjective studies on room acoustics, the fundamental reason for the appreciation of some concert halls remains elusive. This study demonstrates that room acoustic effects contribute to the overall emotional experience of a musical performance. In two listening tests, the subjects listen to identical orchestra performances rendered in the acoustics of several concert halls. The emotional excitation during listening is measured in the first experiment, and in the second test, the subjects assess the experienced subjective impact by paired comparisons. The results showed that the sound of some traditional rectangular halls provides greater psychophysiological responses and subjective impact. These findings provide a quintessential explanation for these halls' success and reveal the overall significance of room acoustics for emotional experience in music performance.